Sodium-glucose cotransporter 2 inhibitors combined with dipeptidyl peptidase-4 inhibitors in the management of type 2 diabetes: a review of current clinical evidence and rationale - Yassin SA; Aroda VR (Dove Medical Press, 2017)
Sayf A Yassin,1 Vanita R Aroda2 1MedStar Union Memorial Hospital, Baltimore, 2MedStar Health Research Institute, Hyattsville, MD, USA Abstract: Type 2 diabetes mellitus (T2DM) is a progressive and multifactorial cardiometabolic disorder. Almost half of adults with diabetes fail to achieve their recommended glucose control target. This has prompted some clinicians to advocate the use of more intensive initial therapy, including the use of combination therapy to target multiple physiologic defects in diabetes with the goal of achieving and sustaining glucose control. Numerous options exist for combining the various classes of glucose-lowering agents in the treatment of T2DM. This report reviews the mechanism, rationale, and evidence from clinical trials for combining two of the newer drug classes, namely, dipeptidyl peptidase-4 inhibitors and sodium-glucose cotransporter 2 inhibitors, and considers the possible role of such dual therapy in the management of T2DM. Keywords: sodium-glucose cotransporter 2 inhibitors, dipeptidyl peptidase-4 inhibitors, type 2 diabetes mellitus, combination therapy